Do HIV-specific CTL continue to have an antiviral function during antiretroviral therapy? If not, why not, and what can be done about it? - McIlroy, Dorian (Frontiers in Immunology, 2013)
Pharmacological re-activation of HIV expression from latent proviruses coupled with fully suppressive anti-retroviral therapy (ART) has been suggested as a strategy to eradicate HIV infection. In order for this strategy to be effective, latently infected cells must be killed either by the cytopathic effect of reactivated HIV gene expression, or by HIV-specific CTL. However, a review of current data reveals little evidence that CTL retain an anti-viral effector capacity in patients on fully suppressive ART, implying that the HIV-specific CTL present in these patients will not be able to eliminate HIV-infected CD4+ T-cells effectively. If this is due to functional impairment or a quantitative deficit of HIV-specific CTL during ART, then therapeutic vaccination may improve the prospects for eradicating latent reservoirs. However, data from the macaque SIV model indicate that in vivo, SIV-specific CTL are only effective during the early stages of the viral replication cycle, and this constitutes an alternative explanation why HIV-specific CTL do not appear to have an impact on HIV reservoirs during ART. In that case, immunotoxins that target HIV-expressing cells may be a more promising approach for HIV eradication.